ANALISIS KELAYAKAN AGRIBISNIS PENGGEMUKAN TERNAK DOMBA DENGAN PAKAN FERMENTASI (STUDI KASUS PENGGEMUKAN TERNAK DOMBA, DI PESANTREN SUNAN KALIJAGA, DESA JOMBLANGAN, WONOCATUR, KABUPATEN BANTUL) (FEASIBILITY ANALYSIS OF LAMB WITH AGRIBISNIS CATTLE FEED FERM - Bharoto, Bharoto; Apsari, Sofia Rieni (Jurnal Ilmu-Ilmu Pertanian, 2012)
This study aims to determine the feasibility of agribusiness livestock feed sheep by fermentation, in terms of profit analysis, O / I ratio and the R / C ratio. The study was conducted at Sunan Kalijaga, Jomblangan village, Wonocatur, Bantul. The study was conducted in May 2011. From the analysis of business profits earned Rp. 63,969,500, for the scale 250 tail, or obtained a profit of Rp 63,969,500, for the scale 250 tail, or in obtaining the advantages / tail Rp 255,878. O / I ratio of 1.29% and 29.9% ROI, so that the results of this analysis concluded that the agribusiness of sheep fattening cattle with feed frermentasi worthy enterprises.